The Cells Growth of Saccharomyces cerevisiae in Substrates of Lignocellulosic Hydrolysate-Added Hydrogen Peroxide Using Turbidimetric Method - Syauqi, Ahmad; Saada, Iqlimatus; Trisna, Adira Tatus; Rodiyanto (Indonesian Journal of Applied Research (IJAR), 2025)
Ethanol was produced reliably using the S cerevisiae yeast for biorefinery as a new renewable energy source (RES). The abundance of lignocellulosic waste (β-glucan) requires its utilization and can be directed to bioethanol-RES production. We focus on hydrolysed polysaccharide fibre from biomass waste that was pretreated with hydrogen peroxide and hydrolisate used for cell growth in the early stages of fermentation activity. The research aims first to compare the initial stages of growth of the Saccharomyces cervisiae cell population in media from the Gracilaria sp macroalgae waste. Second, the consistency of the S cerevisae growth method, namely turbidimetry and cell mass in the early stages of fermentation activity. The research used an experimental method with independent variables as control treatment factor: corn polysaccharide extract (α-glucan 18), lignocellulosic hydrolysate-added peroxide 0.1%, and sugar cane disaccharide granules, seven repetitions for treatment respectively. The control variable was temperature and agitation. Growth parameters used turbidity-cell number and the cell mass tradition for sugar cane disaccharide granules. The determinant of cell number growth according to time is 74.44%; it was estimated that the influence of corn polysaccharides. Lignocellulosic hydrolysate substrate provides growth with a positive slope with a determinant of 39.9%, and both regression slopes were not significantly different and were exponential, while the use of sugar cane disaccharides had a negative slope. The lignocellulosic hydrolysate had a positive potential medium for the growth of Saccharomyces cerevisiae in the early stages of ethanol fermentation.